2021
DOI: 10.1163/15707563-bja10037
|View full text |Cite
|
Sign up to set email alerts
|

No evidence that horn trimming affects white rhinoceros horn use during comfort behaviour and resource access

Abstract: Rhino species use their horns in social interactions but also when accessing resources, rubbing and in interspecific defence. The current poaching crisis has seen southern white rhinos (Ceratotherium simum simum) increasingly dehorned as a conservation management practise, but few studies have evaluated whether the procedure has any behavioural effects. This study sought to document and describe horn-contingent behaviours during resource access, wallowing and rubbing in freeranging white rhinos and establish w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Similar observations were made by Penny et al. (2021) who recorded only two horn rubbing events by horned rhinos in contrast to 31 horn rubbing events by dehorned rhinos. Thus, the effects of dehorning might not be detectable through the rare occurrence of the specific behaviours that involve the horn.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar observations were made by Penny et al. (2021) who recorded only two horn rubbing events by horned rhinos in contrast to 31 horn rubbing events by dehorned rhinos. Thus, the effects of dehorning might not be detectable through the rare occurrence of the specific behaviours that involve the horn.…”
Section: Discussionsupporting
confidence: 88%
“…However, Penny et al. (2021) found no effects of dehorning on rubbing and wallowing and Penny (2019) noted no differences in affiliative and aggressive behaviours between horned and dehorned populations. On the other hand, in a study where rhinos were dehorned because of high aggression and observed before and after dehorning, the number of fights between males was reduced by 68% after dehorning (Patton et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, there were also differences between datasets for uncommon behaviors between detailed researcher and ad hoc keeper data. Horn rubbing (which is known to be rare even for wild rhino and only apparent in detailed datasets that either involve numerous scan samples over a prolonged period or continuous sampling (Penny et al, 2021), was recorded as a rare behavior by researchers but absent from keeper data. This highlights the importance of having detailed data with short times between scans, as found previously by Orban et al (2016) when recording rare behaviors such as pacing (1.4% prevalence) in Giraffe.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the lifecycle of the heterogeneous cloud resource platform is divided, and the feature vector is extracted from different lifecycle stages, and the vector is incorporated into the key to generate the public key and the key as the main medium for the user to access the heterogeneous cloud resources. Then encrypt the user access operation and the transmission data of heterogeneous cloud resources [11]. When the user applies for access operation request to the authorization center, the heterogeneous cloud resource transmission data is encrypted in two layers.…”
Section: Hierarchical Key Management Scheme Design For Heterogeneous ...mentioning
confidence: 99%